2006
DOI: 10.1111/j.1574-6968.2006.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-encoded γ-hexachlorocyclohexane degradation genes and insertion sequences inSphingobium francense(ex-Sphingomonas paucimobilisSp+)

Abstract: The lin genes encode the gamma-hexachlorocyclohexane (gamma-HCH or lindane) catabolic pathway in lindane-degrading strains. The location and stability of these genes have been explored in the lindane-degrading Sphingobium francense strain Sp+, and in two non-lindane-degrading mutants (Sp1- and Sp2-). The lin genes, linA, linB, linE and linX were localized by hybridization on three of the six plasmids of the S. francense strain Sp+ showing dispersal within the genome. The linC gene was detected by PCR, but was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…Furthermore, S. indicum B90A was reported to contain several copies of an insertion sequence, IS6100 (originally isolated from a Gram-positive bacterium, Mycobacterium fortuitum FCI) 16 , which were found to be associated with most of the lin genes in this strain 15 . Recently, several HCH-degrading sphingomonads have been isolated from the HCH contaminated soils from different geographical locations [17][18][19][20][21][22] . These strains were found to contain lin genes highly similar to UT26 and B90A 14,[17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, S. indicum B90A was reported to contain several copies of an insertion sequence, IS6100 (originally isolated from a Gram-positive bacterium, Mycobacterium fortuitum FCI) 16 , which were found to be associated with most of the lin genes in this strain 15 . Recently, several HCH-degrading sphingomonads have been isolated from the HCH contaminated soils from different geographical locations [17][18][19][20][21][22] . These strains were found to contain lin genes highly similar to UT26 and B90A 14,[17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary in S. japonicum UT26, lin genes were found to be dispersed on three circular replicons (linA, linB and linC) on chromosome I and linDER on the conjugative plasmid pCHQ1 [58]. However, in S. francense Sp+, genes linA, linB, linC and linX were shown to be located on three different plasmids [41]. All these studies point out that lin genes are still evolving and are perhaps passed on to sphingomonads through plasmids.…”
Section: Evolution Of Lin Genes To Perform Newer Function In B90amentioning
confidence: 94%
“…Studies on the organization of lin genes in these three strains [8] made it clear that lin genes have entered in sphingomonads from outside sources and do not originally belong to sphingomonads. All these lin genes were subsequently reported to be either present on plasmids or chromosomes [41,58,59]. Additionally, polyphasic approach based taxonomical characterization revealed that these three strains are infact three different species of the genus Sphingobium [38].…”
Section: Evolution Of Lin Genes To Perform Newer Function In B90amentioning
confidence: 98%
See 2 more Smart Citations